Kadar Vitamin C Dan Kualitas Es Krim Tradisional Dengan Penambahan Buah Sirsak Dan Kulit Buah Naga Merah - Melati Putri, Alviyan; , Dra. Suparti, M.Si (2016)
Traditional ice cream in Indonesia known as es es puter or dung-dung. Manufacture of traditional ice cream with twirling container by ice crystals and salt with raw materials such as coconut milk. Traditional soursop ice cream with the addition of red dragon fruit skin is an innovation and improvement of the nutritional value of food. This study aims to determine the quality (taste, texture, flavor and color) and vitamin C traditional ice cream with the addition of red dragon fruit skin. This study uses a completely randomized design (CRD) factorial design with two factors. The first factor is the addition soursop S1 (10 g), S2 (15 g) and S3 (20 g). The second factor is the addition of a red dragon fruit peel K1 (6 g), K2 (11 g), K3 (16 g). Analyzed data using One-way ANOVA. The results showed the highest levels of vitamin C in S3K3 (soursop 20 g: red dragon fruit peel 16 g) worth 4,795 mg. Best organoleptic results in treatment S2K3 (10 g) Soursop fruit : The skin of red dragon fruit 16 g) with the characteristic pink color, typical of soursop fruit flavor, taste quite sweet and the texture is quite soft. The results showed that the addition of soursop fruit and rind of a red dragon affect the levels of vitamin C and quality of traditional ice cream.